Analisis Peran Pemerintah dalam Perekonomian Nasional melalui Tiga Fungsi Utama Fiskal: Alokasi, Distribusi, dan Stabilitas - Putra, Sendi Kurnia; Wahyu Setiani; Dinda Astuti; Wahjoe Pangestoeti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study analyzes the government's strategic role in the national economy through the three main functions of fiscal policy according to Richard A. Musgrave, namely the allocation, distribution, and stabilization functions. Using a descriptive qualitative approach and literature study method, this study highlights how fiscal policy is used to provide public goods and services, create social justice, and maintain economic stability. The study results show that the effectiveness of the implementation of these three functions still faces implementation challenges, such as fiscal constraints, uneven budget distribution, and global economic dynamics. This study emphasizes the importance of adaptive, transparent, and equitable fiscal governance in supporting sustainable national development.